A Multimodal Discourse Analysis of Wonda Coffee TV Commercial - Afriansyah, Rifpan (New Language Dimensions, 2023)
This research involves a Multimodal Discourse Analysis of a commercial video from a famous coffee brand from Malaysia in 2022. This research uses qualitative method and revolves around Halliday’s ideational meta-function and Kress & Van Leeuwen’s representational meaning theory in order to analyze the object of this research. This research is limited only to analyzing the linguistic and visual aspect of the selected commercial to interpret their meanings with multimodal study. The ideational analysis of the selected commercial entitled “Wonderful Colors of Wonda” found that mental process was mostly employed in the video’s utterance. According to ideational meta-function analysis, the commercial video intends to deliver a message about how people unfairly perceive others who are different from them and a possibility of a better society in the future where people would not discriminate others. Within the representational analysis, through conceptual and narrative meaning analysis, the researcher found that the commercial video contains not only a selling-point of a product, but also an implied meaning about social diversity that often happens within our society and who are involved in it. This research is a significant contribution in multimodal discourse analysis on advertisement, as it can prove how important linguistic aspects are when it comes to delivering message through something with multimodality such as commercial video.